2016
DOI: 10.3324/haematol.2015.137125
|View full text |Cite
|
Sign up to set email alerts
|

Helicase-like transcription factor is a RUNX1 target whose downregulation promotes genomic instability and correlates with complex cytogenetic features in acute myeloid leukemia

Abstract: H elicase-like transcription factor is a SWI/SNF chromatin remodeling factor involved in various biological processes. However, little is known about its role in hematopoiesis. In this study, we measured helicase-like transcription factor mRNA expression in the bone marrow of 204 adult patients with de novo acute myeloid leukemia. Patients were dichotomized into low and high expression groups at the median level for clinicopathological correlations. Helicaselike transcription factor levels were dramatically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…On the other hand, we could not detect ASXL1 or RUNX1 mutations in CML patients at initial diagnosis of chronic phase; however, acquisition of RUNX1 and/or ASXL1 mutations occurred in 25.5% (13/51) of patients during AML transformation. Moreover, 3 of the 6 CML-myeloid BC patients carrying ASXL1 mutations had co-existence of RUNX1 and ASXL1 mutations [18]. To further investigate the role of RUNX1 mutations to the myeloid transformation in ASXL1-mutated leukemia, we performed in vitro and in vivo expressing either ASXL1 or RUNX1 single mutant or combination of ASXL1 with RUNX1 mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we could not detect ASXL1 or RUNX1 mutations in CML patients at initial diagnosis of chronic phase; however, acquisition of RUNX1 and/or ASXL1 mutations occurred in 25.5% (13/51) of patients during AML transformation. Moreover, 3 of the 6 CML-myeloid BC patients carrying ASXL1 mutations had co-existence of RUNX1 and ASXL1 mutations [18]. To further investigate the role of RUNX1 mutations to the myeloid transformation in ASXL1-mutated leukemia, we performed in vitro and in vivo expressing either ASXL1 or RUNX1 single mutant or combination of ASXL1 with RUNX1 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that RUNX1 and ASXL1 mutations frequently coexisted in CMML [17]. In addition, we found that the clonal evolution of RUNX1 and/or ASXL1 mutations occurred most frequently in CML with myeloid BC [18]. We had previously shown that the biological activities of RUNX1 mutants predicted sAML transformation from CMML and MDS [19].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanistic studies have revealed that HLTF suppresses the motility of CRC cells via the TGF-β signaling pathway. In 2016, Cheng et al demonstrated that HLTF expression was reduced in adult acute myeloid leukemia patients with more aggressive disease phenotypes (34). In this study, the results of immunohistochemistry revealed that HLTF expression was negatively associated with the differentiation status, tumor invasive depth, lymph metastasis and distant metastasis in CRC.…”
Section: Discussionmentioning
confidence: 55%
“…2g). HLTF, a known SWI/SNF chromatin remodeler in pro-erythroid cells implicated in genomic instability in acute myeloid leukemia 50,54 , also had elevated regulatory activity in Erythroid cells (Fig. 2de) with prominent inferred targets such as BCL11A and UBAC1 35,55 (Fig.…”
Section: Dictys Uncovers Cell-type Specific Grns For Tf Discovery And...mentioning
confidence: 99%
“…Although both differential analyses of Erythroid versus Progenitor cells recovered many established TFs (e.g. GATA1, GFIB, FOXO4 for Erythroid cells and HLF, KLF4 for Progenitors [31][32][33][34][35]46 ), several TFs with Erythroidspecific functions exhibited much stronger logFCs in differential regulation, such as TFCP2 and RREB1 (hemoglobin regulators 47,48 ), HLTF, ZKSCAN3, NFE2L2, etc [49][50][51] (Fig. 2d, Supplementary Table 1).…”
Section: Dictys Uncovers Cell-type Specific Grns For Tf Discovery And...mentioning
confidence: 99%